ANALISIS USAHA KOPI BUBUK CAP AA DI KELURAHAN SIDOREJO KECAMATAN CURUP TENGAH, KABUPATEN REJANG LEBONG - Dwan Pramadani Hidayat; Dwita Frisdinawati; Mira Yanuarti (Lembaga Pengembangan Kinerja Dosen, 2022)
Research on Business Analysis of Cap AA Powdered Coffee in Sidorejo Village, Central Curup District, Rejang Lebong Regency aims to find out how much the production cost of Cap AA ground coffee in Sidorejo Village, Central Curup District, Rejang Lebong Regency, how much revenue and income is obtained and whether the business is The production of Cap AA ground coffee in Sidorejo Village, Central Curup District, Rejang Lebong Regency is efficient. This research was conducted in May 2021 – June 2021 in the Cap Cangkir AA ground coffee industry in Sidorejo Village, Central Curup District, Rejang Lebong Regency. The data analysis method used is cost analysis, revenue, income, R/C Ratio. The cost incurred in the AA stamped coffee powder business is Rp. 29,677,373/month or Rp. 1,978,492/ production. The total revenue from the Cap AA Coffee Powder business is Rp. 37,200,000 per month or an average of Rp. 2.480,000 per production, during the study period with a total operating income of Rp. 7,522,622 per month or an average of Rp. 501,508 per production. The results of the calculation of the R/C Ratio analysis show that the R/C ratio is 1.25. This means that each expenditure of Rp. 1.00 it will generate income of Rp. 1.25. Based on the R/C ratio value obtained with a value of more than 1, it can be said that Mr. Seno's AA powder coffee business is efficient and profitable.